Pemetaan Wilayah Kajian Kelompok Riset: Studi Analisis Tematik di IAIN Syekh Nurjati Cirebon - Badar, Syaeful; Hidayat, Ade (Holistik: Journal for Islamic Social Sciences, 2023)
This study aims to map the study area and analyze the research theme in the research group at IAIN Syekh Nurjati Cirebon. The results of the study mapped out the study areas at IAIN Syekh Nurjati Cirebon divided into five research cluster fields, namely: Indonesian Research, Islam, Social Society, Science and Technology, and Cirebonan.  The five research fields need to be mapped into a superior theme that can describe the potential, characteristics, and uniqueness of research at IAIN Syekh Nurjati Cirebon. The five leading themes are: 1) Strengthening national identity and national competitiveness; 2) Development of awareness and understanding of Islamic insights in strengthening tolerance and peace; 3) Human development and improvement of people's welfare in supporting national integration and social harmony; 4) Development of science and technology with an environmental perspective and local resources; and 5) Development of culture, innovation and creativity of the local wisdom community. The five leading research themes serve as a guide for the formulation of the required research, development and output (product/market) topics. Further elaboration on more specific themes is the implementation of a research strategy in the context of scientific development at IAIN Syekh Nurjati Cirebon who wants to develop research in the religious (Islamic) sciences which has so far existed in the area of monoscience, to be changed to be multidisciplinary and interdisciplinary.